Classics of Western philosophy (Hackett Publishing Company, 2002)
This anthology is by far the best anthology of its kind. If you love ancient and medieval philosophy the way I do, it is possible to teach an entire semester "intro. to phil." course out of Plato, Aristotle, Sextus, Augustine, Anselm, Aquinas, Maimon, Ockham, Gerson, and the Stoa